2019
DOI: 10.1084/jem.20170277
|View full text |Cite
|
Sign up to set email alerts
|

CCL22 controls immunity by promoting regulatory T cell communication with dendritic cells in lymph nodes

Abstract: Rapp et al. demonstrate that dendritic cells in the lymph node secrete CCL22 to build cell–cell contacts with CCR4-expressing regulatory T cells, leading to immune suppression. Conversely, CCL22 deficiency results in enhanced T cell immunity, shown here in the setting of vaccination, cancer, and inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
138
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 59 publications
8
138
1
Order By: Relevance
“…CCL22 is induced by the Th2 cytokines IL-4 and IL-13 [8]. CCL22 is also identified as a T-regulatory-associated chemokine [23], by promoting regulatory T cell communication with dendritic cells in lymph nodes [24].The present study showed an elevated level of CCL22 in patients with hyperprolactinemia compared with healthy controls. Hyperprolactinemia patients also showed a higher level of the B cell attracting chemokine CXCL13, and prolactin levels correlated positively with both CCL22 and CXCL13.…”
Section: Discussionsupporting
confidence: 55%
“…CCL22 is induced by the Th2 cytokines IL-4 and IL-13 [8]. CCL22 is also identified as a T-regulatory-associated chemokine [23], by promoting regulatory T cell communication with dendritic cells in lymph nodes [24].The present study showed an elevated level of CCL22 in patients with hyperprolactinemia compared with healthy controls. Hyperprolactinemia patients also showed a higher level of the B cell attracting chemokine CXCL13, and prolactin levels correlated positively with both CCL22 and CXCL13.…”
Section: Discussionsupporting
confidence: 55%
“…More importantly, human LN DCs are understudied and even though we were unable to decipher more than one LN DC cluster, there is a wealth of genetic information provided in this datum. For instance, CCL17 and CCL22 expression is restricted to DC populations in lung and LNs, and not expressed on human blood DCs 65,66,67,68 . This is also true in mice, where these chemokines distinguish DCs from other immune cell types and are important for T cell recruitment and interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Expression level augmentation has notably been observed for proinflammatory cytokines such as CCL11 and CCL22 (Fig. 8) which are different chemokines needed to recruit cells populations from immune system [45]. IFNγ and TNFα also showed an increase in expression level, which are well known proinflammatory cytokines.…”
Section: Common Toxicity Mechanism Of Mwcntmentioning
confidence: 91%
“…Venn diagrams based on transcriptomic analysis results showing the number of common genes dysregulated[45] after NR8383 cells exposure to three MWCNT and the number of genes specific to each exposure at fold change, FC ≥ 1.5 (70 for NM403, 38 for NRCWE-042 and 2876 for NRCWE-049). The main biological process (Gene ontology) common a specific for MWCNT studied were presented (DAVID analysis) Nahle et al J Nanobiotechnol (2020)18:36 …”
mentioning
confidence: 99%